Bionanotechnology : principles and applications - Anal, Anil Kumar; Taylor and Francis (Boca Raton, FL : CRC Press, an imprint of Taylor and Francis, 2018)
This book deals with a subject of high interest and importance in all sectors, including biomedical, food, agriculture, energy, and environment. Biological systems are essential in nanotechnology, and many new applications are being developed by mimicking the natural systems. Approaching these topics from an engineering perspective, the book offers insight on the details of nanoscale fabrication processes as well as cell biology. The basics of biology and chemistry, with a focus on how to engineer the behavior of molecules at the nanoscale, are also explored and analyzed. The aim of the text is to provide the reader with broader knowledge of biological methods for signal transduction and molecular recognitions systems and how they can be replicated in bio-sensing applications. The reader will learn the basic structures and interactions of biomacromolecules for developing biocompatible and eco-friendly devices.
chapter 1 Bionanotechnology and Cellular Biomaterials / Anil Kumar Anal -- chapter 2 Nanostructured Cellular Biomolecules and Their Transformation in Context of Bionanotechnology / Anil Kumar Anal -- chapter 3 Genomics and Bionanotechnology / Anil Kumar Anal -- chapter 4 Protein Engineering and Bionanotechnology / Anil Kumar Anal -- chapter 5 Immune Systems, Molecular Diagnostics, and Bionanotechnology / Anil Kumar Anal -- chapter 6 Bionanofabrication and Bionano Devices in Tissue Engineering and Cell Transplantation / Anil Kumar Anal -- chapter 7 Immobilization of Biomolecules / Anil Kumar Anal -- chapter 8 Nanostructure-Based Delivery Dosage Forms in Pharmaceuticals, Food, and Cosmetics / Anil Kumar Anal -- chapter 9 Nanoparticles, Biointerfaces, Molecular Recognition, and Biospecificity / Anil Kumar Anal.
Keywords: Nanobiotechnology; SCIENCE / Biotechnology; TECHNOLOGY & ENGINEERING / Material Science